Placement of implants in an ossifying fibroma defect obliterated with demineralized, freeze-dried bone allograft and Plasma-rich growth factor - Umashankar Pal; Niraj Mishra (Wolters Kluwer Medknow Publications, 2012)
There has been considerable clinical interest in combining the grafts, particularly bone allografts for support for dental implants, soft-tissue support, periodontal maintenance, and ovate pontic formation. The use of demineralized, freeze-dried bone allograft (DFDBA) offers certain advantages over other graft materials and can avoid the need for a second-site surgery for autogenous donor bone. The advantages of DFDBA include handling properties, osteoinductivity, membrane tenting, and less susceptibility to migration after placement. This article will review available grafting materials and demonstrate a case of ossifying fibroma of the mandible, which was treated by curettage and hollow cavity filled with DFDBA. Six months follow-up period showed successful graft result and this grafted bone form was utilized for implant supported prosthesis.